2020
DOI: 10.4317/jced.56764
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of bonded premolars to four artificial ageing models post enamel conditioning with a novel calcium-phosphate paste

Abstract: Bond strength to calcium-phosphate treated enamel e317

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
(54 reference statements)
1
12
0
Order By: Relevance
“…One-month water storage (1 MW): the samples were kept in distilled water (pH=6) for 30 days at 37°C and the distilled water was replenished daily [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…One-month water storage (1 MW): the samples were kept in distilled water (pH=6) for 30 days at 37°C and the distilled water was replenished daily [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ibrahim et al explained that when Ca–P-based materials are included in the etching solution, phosphate is buffered, causing the re-precipitation of Ca–P and simultaneously limiting the demineralization of the enamel by acidic solutions. Another study by Ibrahim et al using a Ca–P-based etchant also found that enamel conditioned with an acidic Ca–P paste (β-tricalcium phosphate and monocalcium phosphate monohydrate powders mixed with 37% H 3 PO 4 solution) achieved adequate bond strength with minimal or no adhesive residue or enamel damage ( Ibrahim et al, 2020 ). In a study by Ibrahim et al, the pH was increased from 0.8 to 1.4 after mixing Ca–P powder in 35% H 3 PO 4 , and this resulted in a less aggressive etchant that prevented enamel demineralization through a buffering effect and improved adhesion ( Ibrahim et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to overcome these iatrogenic factors while preventing the loss of minerals: remineralizing or preventing demineralization by supplying fluoride ( Jablonski-Momeni et al, 2020 ; Aldhaian et al, 2021 ; Althagafi, 2022 ), including components for remineralization in pretreatment materials such as adhesives ( Liu et al, 2018 ; Wang et al, 2018 ; Yang et al, 2022 ), processing adhesives prior to pretreatment of remineralizing materials such as casein phosphopeptide-amorphous Ca–P (ACP) or bioactive glass ( Ladhe et al, 2014 ; Mobarak et al, 2015 ; Bakry and Abbassy, 2019 ; Abbassy et al, 2021 ; Aref and Alrasheed, 2022 ), and the use of Ca or Ca–P-based materials in the enamel etching solution ( Ibrahim et al, 2019 ; Ibrahim et al, 2020 ; Tuma and Yassir, 2021 ). Ibrahim et al (2019 ) reported the development of an etchant paste prepared by mixing β-tricalcium phosphate and monocalcium phosphate monohydrate powder with 35% H 3 PO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…(5) Once the bonding procedures were completed, the bonded teeth of first group were stored in the incubator in distilled water inside sealed containers at 37°C for 30 days with daily refreshment, in order to avoid the cumulative effects. (12,13) While the bonded teeth in the second group stored in deionized water for 24 hours at 37°C prior to the acidic challenge experiment. The acidic solution (pH=2.5) of 500 ml was prepared by gradual addition of 1.5 ml of HCl [1M] in distilled water.…”
Section: Fluoride Releasing Bond With Self-etching Primermentioning
confidence: 99%
“…After each session, each storage medium was periodically renewed, and before and after each session, the samples were rinsed with water and air dried. (13)…”
Section: Fluoride Releasing Bond With Self-etching Primermentioning
confidence: 99%